2018
DOI: 10.4193/rhinol/18.077
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and omalizumab: eosinophils not IgE predict treatment response in real-life

Abstract: Background: Chronic rhinosinusitis with and without nasal polyps (CRSwNP and CRSsNP respectively) can be difficult to treat and biologics offer potential as a future therapeutic intervention. CRS and severe asthma often co-exist. Omalizumab is currently licenced for the treatment of severe allergic asthma. Objective: The aim was to determine which blood biomarkers and treatment variables were associated with clinical response for sinonasal symptoms in patients with allergic CRSsNP and CRSwNP who were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…Reduction in blood eosinophils has also been demonstrated following omalizumab therapy in CRSwNP. 45 Other off-label use of omalizumab in various "nonallergic" conditions has found similar findings with respect to clinical improvements. Similar to observations in allergic asthma, reductions in the numbers of blood and tissue eosinophils were reported in patients with eosinophilic gastroenteritis following omalizumab treatment.…”
Section: Mechanism Of Omalizumabmentioning
confidence: 72%
See 2 more Smart Citations
“…Reduction in blood eosinophils has also been demonstrated following omalizumab therapy in CRSwNP. 45 Other off-label use of omalizumab in various "nonallergic" conditions has found similar findings with respect to clinical improvements. Similar to observations in allergic asthma, reductions in the numbers of blood and tissue eosinophils were reported in patients with eosinophilic gastroenteritis following omalizumab treatment.…”
Section: Mechanism Of Omalizumabmentioning
confidence: 72%
“…Our own group analysed what factors predicted CRS clinical response in a real-life study. 45 Here, all patients had severe asthma, were sensitised to at least one perennial aeroallergen and had a median eosinophil count of 0.45 x 10 9 /L. Importantly, 75% patients had NERD and therefore represented the more severe, difficult to treat CRSwNP subtype.…”
Section: Outstanding Questionsmentioning
confidence: 81%
See 1 more Smart Citation
“…We have previously shown that omalizumab treats CRS and asthma together in this group of patients 26 ,. 27 As far as we are aware, this is the first real‐life extension study to show that treatment with omalizumab in patients with CRS and severe asthma significantly improved anxiety but had no impact on depression. This was despite improvements in all measures of upper and lower airway disease control.…”
Section: Discussionmentioning
confidence: 80%
“…Both small studies (<30 patients) did not show impact on disease-specific QoL, but one study did show effect on the physical domain of short form-36 (SF-36) and asthma quality of life questionnaire (AQLQ), CRS symptom scores, and nasal polyp score [77]. A small real-life study showed that improvements are greater in those with eosinophilic disease and not based on IgE [80].…”
Section: Dupilumab Compared To Other Biologicalsmentioning
confidence: 98%